Infantile small cell gliomas - Friede, R L; Janzer, R C; Roessmann, U (Acta neuropathologica, 1982)
Fourteen juvenile patients with small cell gliomas were studied at two institutes. These tumors are believed to form a distinct entity. They arise mostly in the diencephalon or the brain stem and are composed of a poorly differentiated small cell component having a pronounced tendency to differentiate into a glioma. Signs of neuroblastic differentiation were also found with the electron microscope. Small cell gliomas disseminate early and profusely throughout the ventricular walls and the subarachnoid spaces including the spinal meninges. Prognosis is grave, most patients dying within 1 year of diagnosis or surgical intervention. The designation "infantile small cell glioma" overlaps with both the "metastasising gliomas in young subjects" of Eade and Urich (1971) and with the primitive neuroectodermal tumor of infancy of Hart and Earle (1973).